The Provisions of Professional Zakat; Between Zakat on Agricultural Products and Zakat on Gold - Hidayat, Muhammad; Roni, Muhammad (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Professional zakat is a new problem in the field of fiqh, and the issue of professional zakat is hotly discussed, starting from its understanding and legal basis to the procedures for its implementation. This article is classified as literature research with a qualitative approach. The methodology used is a comparative study of law. The results of the study concluded that there were differences among scholars on professional zakat in terms of its legal basis; some scholars mentioned departing from the construction of qiyas against al-mal al-mustafad. Others say that the basis is Q.S. Al-Baqarah/2:267. While in terms of implementation, some scholars argue that the qiyaskan nisab and qadar zakat professions are the same as agricultural zakat, which does not require hauling. Others argue that the nisab and qadar zakat professions are the same as nisab and qadar zakat al-mal al-mustafad, which is 85 grams of gold but does not require hauling, while zakat al-mal al-mustafad requires hauling. There are also scholars who argue that the nisab and qadar zakat professions are qiyaskan to nisab and qadar zakat gold and wear haul.